IDENTIFIKASI NILAI KONSTANTA DAUN TANAMAN ALPUKAT DAN MANGGIS BERBASIS PENGOLAHAN CITRA DIGITAL - Mustopa, Zaen Ali; Al Ramadhani, Farchan Mushaf; Badrudin, Ubad (Fakultas Pertanian Universitas Janabadra, 2025)
Leaves are essential organs in plant physiology as they store unique morphometric information for each variety. The leaf constant is an important parameter because it can be used to efficiently estimate leaf area. This study aimed to identify the leaf constant values of avocado variety Hass and mangosteen variety Kaligesing using digital image processing methods. The research was conducted at the Agrotechnology Laboratory, University of Pekalongan. Leaf images were calibrated and processed using ImageJ software to obtain leaf area values. The leaf constant was found to be 0.722 for avocado and 0.661 for mangosteen. These constants were then used to predict leaf area, which was validated against measured leaf area from digital image processing using statistical analysis. The results showed determination coefficients (R²) of 0,9984 for avocado and 0,9915 for mangosteen, with RMSE, NRMSE, NSE, and d values indicating a very high level of agreement. This study demonstrates that leaf constants obtained through digital image processing can be used to model leaf area accurately, quickly, and non-destructively.